2021
DOI: 10.1007/s11696-020-01478-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel pregnane-based 20-carboxamides via palladium-catalysed aminocarbonylation

Abstract: Abstract20-Carboxamidopregnene derivatives, such as 3β-acetoxy-5α-pregn-20-ene-20-carboxamides and 5α-pregn-20-ene-20-carboxamides were synthesized from the widely accessible 3β-acetoxy-pregn-5,16-dien-20-one (PDA) using selective hydrogenation, hydrazine and iodoalkene formation, as well as palladium-catalysed aminocarbonylation. The 20-iodo-20-ene derivatives, obtained from the corresponding 20-keto derivatives via their hydrazones, served as substrates. 23 new 20-carboxamides were obtained using various N-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The same authors reported the aminocarbonylation of steroidal substrate pregna‐20‐iodo‐20‐ene, [ 87 ] prepared also from its corresponding 3α‐acetoxy‐pregna‐5,16‐dien‐20‐one by Barton's method (Scheme 36). The iodoalkene functionality was aminocarbonylated with several primary and secondary amines as N ‐nucleophiles, using Pd(OAc) 2 /PPh 3 as catalyst and 1 bar CO, in the presence of triethylamine as base.…”
Section: Synthesis Of Fine Chemicals Using Comentioning
confidence: 99%
“…The same authors reported the aminocarbonylation of steroidal substrate pregna‐20‐iodo‐20‐ene, [ 87 ] prepared also from its corresponding 3α‐acetoxy‐pregna‐5,16‐dien‐20‐one by Barton's method (Scheme 36). The iodoalkene functionality was aminocarbonylated with several primary and secondary amines as N ‐nucleophiles, using Pd(OAc) 2 /PPh 3 as catalyst and 1 bar CO, in the presence of triethylamine as base.…”
Section: Synthesis Of Fine Chemicals Using Comentioning
confidence: 99%
“…20-Carboxamidopregnene derivatives, such as 3β-acetoxy-5α-pregn-20-ene-20carboxamides and 5α-pregn-20-ene-20-carboxamides were synthesized from the corresponding iodoalkenes and various N-nucleophiles (Figure 17). The iodoalkenes were produced in multistep reactions, namely selective hydrogenation, the reaction of the subsequent ketones with hydrazine, and the conversion of the hydrazones to iodoalkenes with iodine [78]. 17-Formyl-androst-16-ene and its analogues were synthesized from the corresponding 17-iodo-16-ene derivatives in Pd-catalyzed formylation reactions in the presence of CO. Tributyltin hydride served as a hydrogen source.…”
Section: Preparation Of Carbonyl Compounds With Steroid Scaffoldsmentioning
confidence: 99%